2002
DOI: 10.1029/2001gb001466
|View full text |Cite
|
Sign up to set email alerts
|

Interannual growth rate variations of atmospheric CO2 and its δ13C, H2, CH4, and CO between 1992 and 1999 linked to biomass burning

Abstract: [1] High-precision, multispecies measurements of flask air samples since 1992 from CSIRO's global sampling network reveal strong correlation among interannual growth rate variations of CO 2 and its d 13 C, H 2 , CH 4 , and CO. We show that a major fraction of the variability is consistent with two emission pulses coinciding with large biomass burning events in 1994/1995 and 1997/1998 in tropical and boreal regions, and observations of unusually high levels of combustion products in the overlying troposphere a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
279
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(304 citation statements)
references
References 100 publications
(167 reference statements)
22
279
2
1
Order By: Relevance
“…Biomass burning is anticorrelated with precipitation, reinforcing the land NPP driven response to ENSO. Modeled global IAV in natural biomass burning agrees with Langenfelds et al [2002] and Duncan et al [2003] in predicting maxima and minima emissions in years 1994/1995 and 1995/1996, respectively. Extremely high emissions in 1997/1998, largely associated with fires in southeast Asia [van der Werf et al, 2003], are not captured by LPJ.…”
Section: Tropical and Southern Hemisphere Fluxessupporting
confidence: 55%
“…Biomass burning is anticorrelated with precipitation, reinforcing the land NPP driven response to ENSO. Modeled global IAV in natural biomass burning agrees with Langenfelds et al [2002] and Duncan et al [2003] in predicting maxima and minima emissions in years 1994/1995 and 1995/1996, respectively. Extremely high emissions in 1997/1998, largely associated with fires in southeast Asia [van der Werf et al, 2003], are not captured by LPJ.…”
Section: Tropical and Southern Hemisphere Fluxessupporting
confidence: 55%
“…From this the Allan variance was computed. The Allan variance, a method for computing the frequency stability of clocks, can also be used to analyze the noise of a sensor (Siraya, 2001;Land et al, 2007). Allan variance is given as…”
Section: Sensor Stabilitymentioning
confidence: 99%
“…where τ is the sampling interval, N is the number of measurements of some quantity T i , and n is the number of adjacent values of T i in τ (Land et al, 2007). Akin to the standard deviation, the Allan deviation is the square root of the variance,…”
Section: Sensor Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The Northern Hemisphere dominates the annual cycle of CO 2 concentration because it has much greater land area and plant biomass than the Southern Hemisphere (Yu et al, 2014). CO 2 emissions from forest fires in the tropical and boreal region have also been found to contribute the interannual variablity in the CO 2 growth rate (Langenfelds et al, 2002;Patra et al, 2005;Zhang et al, 2007). It is also interesting to note that Gray et al (2014) and Zeng et al (2014) have shown that the intensification of agriculture may have been a key contributor to the increase in atmospheric CO 2 seasonal amplitude.…”
Section: Introductionmentioning
confidence: 99%